Экспериментальное исследование реакции жесткой плиты на удар птицей - Ярещенко, В. Г. (НТУ "ХПИ", 2014)
Работа посвящена вопросам экспериментального исследования реакции жесткой плиты на удар птицей методом динамического широкополосного тензометрирования. Приведены данные экспериментальных исследований влияния кинематических факторов на реакцию деформируемой преграды при столкновении с птицей. Проведена серия экспериментов по определению деформаций плоской преграды при ударе тушкой птицы. Экспериментально исследовано влияние скорости и угла соударения на максимальные деформации преграды.

The problem of experimental study of the reaction of rigid plates on a bird strike by dynamic broadband strain measurement are considered in work. Data of experimental researches of influence of kinematical factors on response of a deformable plate-target at collision with a bird are presented. A series of experiments by definition of deformations of a flat plate are carried out at impact by the birds. Influence of different impact angles and velocities on maximum deformations of target is investigated. Extensive full-scale experiments in investigating the response of a plate have demonstrated that the maximum plate strain values decrease with decreasing impact angle. It is shown that, with increasing velocity of the fired object, the plate strain grows, the strain vs. velocity dependence being close to a quadratic one. Experimental date, obtained by using the dynamic wide-range strain measurement technique, are in good agreement with theoretical results.
Experimental research of the reaction of rigid plates on bird strike
Keywords: тензометрия; деформация; динамика; strain gauges; deformation; dynamics